Pengaruh Variasi Media Pertumbuhan terhadap Aktivitas Peredaman Radikal Bebas DPPH Ekstrak Kapang Endofit Isolat Cb.D1 - Purnamasari, Ayu; Andriyaningsih, Fitri; Pamungkas, Riska Andriani; Septiana, Eris (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Endophytic fungi are a source of antioxidant compounds in nature. The low yield of extracts and active compounds produced is one of the limiting factors for using endophytic fungi as a source of natural antioxidant compounds. Modification of growth media is an alternative solution to overcome this problem. This study aimed to determine the effect of media conditions, belonging to carbon and nitrogen sources and different initial pH of fermentation, on the antioxidant through DPPH radical scavenging activity of extract of endophytic fungi Cb.D1 isolated from cinnamon plant leaves. The culture was propagated using Czapek Dox Broth basal liquid medium with agitation speed 120 rpm at room temperature for 14 days. The carbon sources used were glucose, sucrose, and soluble starch. The nitrogen sources were natrium nitrate, ammonium nitrate, and yeast extract. The initial pH conditions used were 5, 7, and 9, and ethyl acetate as the extraction solvent. The results obtained that the variation of nitrogen and carbon sources and also initial pH conditions can increase the yield of extract of endophytic fungi Cb.D1. Glucose, yeast extract, and initial pH at 9 were the best growth media to gain it. The substitution of nitrogen sources and initial pH can increase the DPPH free radical scavenging activity of endophytic fungal extract compared to substitution for carbon sources. The highest activity from the Cb.D1 endophytic fungal extract was obtained from media that contain sucrose and natrium nitrate as a carbon and nitrogen sources and an initial pH of 5. The Variation of growth media of endophytic fungi Cb.D1 affected their extract in DPPH free radical scavenging activity.